The Influence of the BALAGAR Strategy on the 3rd Grade Students of SD Negeri 006 Sosor Gonting in Understanding Sentence Meaning - Hutkem Repelina; Rudy; Yenita Br Sembiring (Linguistic, English Education and Art (LEEA) Journal, 2026)
This study aimed to determine the effect of the BALAGAR (Read Scene Picture) strategy on the sentence meaning comprehension ability of 3rd-grade students at UPT SD Negeri 006 Sosor Gonting and to compare the learning outcomes of students using the BALAGAR strategy with those using conventional methods. This study used a quantitative method with a quasi-experimental design. The research population involved all 35 third-grade students from UPT SD Negeri 006 Sosor Gonting, divided into experimental and control classes. Data collection techniques were carried out thru pretest and posttest, observation, and questionnaires. Data analysis was conducted using SPSS 29 software thru normality tests, homogeneity tests, hypothesis tests, and N-Gain analysis. The research results indicate that the BALAGAR strategy significantly affects the improvement of students' sentence meaning comprehension skills. This is evidenced by the hypothesis test results with an Asymp. Sig value < 0.05, thus H₀ is rejected and H₁ is accepted. The average score of the experimental class increased from 67.65 to 90.59, while the control class decreased from 46.11 to 40.56. The N-Gain analysis results for the experimental class obtained an average score of 0.7216 with a high category, while the control class obtained a score of -0.3068. Thus, the BALAGAR strategy has proven effective in improving the sentence meaning comprehension skills of third-grade elementary school students.  Keywords: BALAGAR Strategy, Read Picture Plays, Sentence Meaning Comprehension, Reading Literacy, Interactive Learning. Keywords: BALAGAR Strategy, Read Picture Plays, Sentence Meaning Comprehension, Reading Literacy, Interactive Learning.